Transcendent and Immanent God: Tetun Tribe Divine Concept "Nai Maromak" Millennial Perspective - Lau, Stefanus; Sermada, Donatus; Nikodemus, Nikodemus (International Journal Ethnic, Racial and Cultural Heritage, 2024)
The focus of this study is to examine the concept of divinity of the Tetun tribe "Nai Maromak" from the perspective of the Millennial Generation. The analytical methodology used is comparative analysis to compare and analyse the similarities and differences between the concept of divinity of the Tetun tribe and the Millennial Generation, especially in terms of the transcendent and immanent nature of God. The researcher used this method in the following ways: Identifying the concept of divinity of the Tetun tribe through in-depth interviews with traditional leaders and Millennial Generation Representatives as well as through literature study. Then comparing the concept of divinity between the Tetun tribe and the Millennial Generation by identifying similarities and differences. The research perspective used is a philosophical perspective to understand the concept of divinity from a philosophical point of view. This study found that the concepts of divinity of the Millennial Generation and the Tetun tribe, especially in terms of the transcendent and immanent nature of God, have both similarities and differences. The findings of this research also contribute to Tetun Catholics as well as Catholic millennials to be more firm in their faith in God according to the concept taught by the Catholic ChurchKeywords:  Tetun tribe's, Catholic Millennials, transcendence, immanence.